多時期ステレオペア画像を用いた南極昭和基地近傍の氷床縁変動の検出 - 澤, 柿教伸; 駒沢, 晧; Takanobu, Sawagaki; Kou, Komazawa (2013)
Existing aerial photographs and satellite images are usefull to show cryospheric responses to the climate changes. While recent satellite altimetry has allowed mapping of elevation change for most of continental Antarctica for more than a decade, the marginal fluctuation of the Antarctic ice-sheet, such as the Soya Coast in the vicinity of Syowa Station, remain unquantified because the ice slopes of the coastal area are too steep or unsignificant for existing sensors resolution. There is an archive of aerial photographs going back to the IGY (1956) for parts of the Enderby Land, East Antarctica, taken by the Japanese Antarctic Research Expeditions (JARE). Photogrammetry of time-series of these photographs is now the only way to reconstruct changes in glacier surface height and terminal fluctuations. We have already established methods for measuring glacier volume change using time-series photogrammetry to comparison of Digital Elevation Models (DEMs) of glacier surfaces using digital photogrammetry and GIS systems. However, for the vicinity of Syowa Station, the old aerial photographs have been difficult to use for detailed measurements. Overcoming the problems hindering accurate photogrammetry could reveal a vast archive of glacier change measurements spanning 50 years. We introduce our attempt to develop a newly-acquired, highly-accurate photogrammetric model, showing our a worked example of 2 epochs of aerial photography in 1991 and ALOS images in 2007, and a preriminal assessment of the achievable measurement accuracy. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 統計数理研究所 ３階セミナー室１（D305） conference object